Quantitative Analysis of Residual Tetracyclines in Buffalo Meat using RP-HPLC - Kalpana, S.; Muthukumar, M. (Journal of Meat Science, 2019)
A liquid chromatographic method is described for the simultaneous quantitative measurement of oxytetracycline and chlortetracycline in  buffalo meat. After extraction of the meat samples using Mcllvaine buffer – EDTA solution and SPE clean up, the analysis of the antimi crobials was carried out using a reverse phase HPLC using UV detector. The chromatographic separation was accomplished with mobile  phase consisting of 0.1M oxalic acid, methanol and acetonitrile (70:15:15, v/v) in an isocratic elution mode. The volume of injection and  flow rate of the mobile were 1.5 ml/min and 50 µl respectively.UV detector was operated at a wavelength 360nm. Linearity, recovery,  selectivity, limit of detection, limit of quantification was evaluated in buffalo meat matrix at drug concentrations ranging from 25-1000  ng/g. Mean extraction recoveries of oxytetracycline and chlortetracycline were in the range of 90-97 %. The limits of quantification for  oxytetracycline and chlortetracycline were 38.30 and 36.63 µg/kg, respectively. The proposed RP-HPLC method is quite adequate for  routine analysis of residual tetracyclines in buffalo meat below Codex MRL of 200 µg/kg.
Keywords: RP-HPLC; Buffalo meat; Tissue residues; oxytetracycline; chlortetracycline